An Analysis of the Effectiveness of the Policy of Allocation on Income Tax Incentive Covered by the Government in the Context of Handling Corona Virus Disease 2019 (A Case Study of West Bekasi KPP Pratama in 2020) - Mainita Hidayati Keman; Cintya Safira Putri; Wuwuh Andayani; Vandyarman Mulya Priyanda (Yayasan Ilomata, 2022)
The background of this study was Pandemic Covid-19 which created some effects on the economic or taxation sectors. Also, it gave an impact on the decline of companies’ income which led to cutting the salaries of many employees and termination of the working relationship. Thus, it required the government to allocate the incentives PPh 21 DTP to relieve the burden on taxpayers and can help restore people's purchasing power. The purpose of this study was to analyze the policy of allocation of PPh 21 DTP incentives in the context of handling Corona Virus Disease 2019 at West Bekasi KPP Pratama based on an analysis of effectiveness, obstacles faced and efforts made to overcome obstacles. This research was descriptive qualitative. The data collection was using observation, documentation, and interviews. The results of this study were that allocating PPh 21 DTP on West Bekasi KPP Pratama was still not effective because many taxpayers did not take advantage of this incentive because of the lack of information and socialization given. This was based on the achievement of objectives, integration, and adaptation. The obstacles encountered were the socialization was less rigorous as many taxpayers were ill-informed, many taxpayers who did not take advantage of the policy well, and the lack of awareness of mandatory taxes by not reporting the realization of the utilization of PPh 21 DTP. Last, the efforts made by KPP Pratama, West Bekasi were to conduct socialization thoroughly and maintain the synergy/cooperation between the KPP and the taxpayers.